Odpowiedzi

2010-03-19T22:51:10+01:00
A)2t-(3t+1)=6
2t-3t-1=6
2t-3t=6+1
-t=7/:(-1)
x=-7
b)3(y+6)-y=2(y+9)
3y+18-y=2y+18
3y-y-2y=18-18
0=0
c)(x-7)-2(3x+5)=3
x-7-6x-10=3
x-6x=3+7+10
-5x=20/:(-5)
x=-4
d)6(¼x-2)=18
1,5x-12=18
1,5x=18-12
1,5x=6/:1,5
x=4
e)nie zrobię ci tego przykładu bo nie wiem jakie tam są liczby
Najlepsza Odpowiedź!
2010-03-19T22:51:11+01:00
A) 2t-(3t+1)=6
2t-3t-1=6
-t=6+1
-t=7 |*(-1)
t=-7

b) 3(y+6)-y=2(y+9)
3y+18-y=2y+18
2y-2y=18-18
0=0

c) (x-7)-2(3x+5)=3
x-7-6x-10=3
-5x=3+17
-5x=20 |/(-5)
x=-4

d) 6(¼ x-2)=18
1½x-12=18
1½x=18+12
1½x=30 |*(⅔)
x=20

e) x /6-⅙=1 |*6
x-1=6
x=7